2021
DOI: 10.1186/s12884-021-03834-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNAs for pro-and anti-apoptotic factors in granulosa cells and follicular fluid of women undergoing in vitro fertilization. A pilot study

Abstract: Background This observational clinical study evaluated the expression levels and predictive values of some apoptosis-related genes in granulosa cells (GCs) and follicular fluid (FF) of women undergoing in vitro fertilization (IVF). Methods GCs and FF were obtained at oocyte retrieval from 31 consecutive patients with heterogeneous infertility diagnosis (age: 34.3 ± 5.8 years, body mass index: 24.02 ± 3.12 kg/m2, duration of infertility: 4.2 ± 2.1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…[22] Clinical trials in the eld of domestic ART (primarily in vitro fertilization, IVF) have shown signi cant results in terms of IVF e cacy. [23][24][25][26] Unintended childlessness is a major problem at both the individual and societal levels. [27] It can also place an increased burden on the women and couples concerned, as well as on healthcare and health insurance systems, especially in countries where the range of publicly funded services is currently limited.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Clinical trials in the eld of domestic ART (primarily in vitro fertilization, IVF) have shown signi cant results in terms of IVF e cacy. [23][24][25][26] Unintended childlessness is a major problem at both the individual and societal levels. [27] It can also place an increased burden on the women and couples concerned, as well as on healthcare and health insurance systems, especially in countries where the range of publicly funded services is currently limited.…”
Section: Introductionmentioning
confidence: 99%